The Aisyiyah Child Protection Model: A Retrospective Life-Course Analysis of Maqâshid al-Syarî‘ah in Adolescent Pregnancy - Betra Sarianti; Linda Safitra (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2026)
This article examines the Aisyiyah Child Protection Model as a transformative framework for addressing teenage pregnancy within Islamic family law in Indonesia, moving beyond formal legal marriage. Driven by the high number of requests for marriage dispensations, this study aims to evaluate the effectiveness of this non-marital support ecosystem against the legalistic enforcement of the Religious Court. Employing a qualitative-empirical approach within a retrospective life-course analysis, data were collected from a qualitative content analysis of 408 marriage dispensation case files at the Class 1A Religious Court of Bengkulu (2020-2024), alongside in-depth, open-ended interviews with key institutional and community informants. These informants included executives of Majelis Kesejahteraan Sosial (MKS) Aisyiyah, professional social workers (Peksos), religious court judges, biological/adoptive parents, and the Head of Neighborhood Unit 16 in Rawa Makmur, Bengkulu City, who served as a 25-year community historical witness for past retrospective cases. The findings reveal a judicial paradox where judges granted 100% of dispensation petitions due to emergency pregnancies and intense parental pressure to conceal social stigma, which conversely triggered high school dropout rates and long-term socio-economic vulnerability. Conversely, the Aisyiyah Protection Model has proven highly successful in the long term. By enforcing strict conditionality for absolute educational continuity, utilizing structured family economic empowerment, and leveraging community-backed foster care systems, the model successfully secures the dimensions of hifz al-nafs (protection of life) and hifz al-nasl (protection of lineage). Longitudinal evidence demonstrates that by bypassing forced marriage, teenage mothers successfully achieved university degrees while their children transitioned into adulthood (16-20 years old) with a stable, multidimensional quality of life (hayat tayyibah). Artikel ini mengkaji Model Perlindungan Anak Aisyiyah sebagai kerangka kerja transformatif dalam menangani kehamilan remaja dalam ranah hukum keluarga Islam di Indonesia, dengan melangkah melampaui formalitas pernikahan legal. Dipicu oleh tingginya permohonan dispensasi kawin, studi ini bertujuan untuk mengevaluasi efektivitas ekosistem pendampingan non-marital ini terhadap penegakan legalistik di Pengadilan Agama. Menggunakan pendekatan kualitatif-empiris dengan analisis alur-hidup retrospektif (retrospective life-course analysis), data dikumpulkan melalui analisis isi kualitatif terhadap 408 berkas perkara dispensasi kawin di Pengadilan Agama Kelas 1A Bengkulu (2020-2024), serta wawancara mendalam dan terbuka dengan informan kunci institusional dan komunitas. Informan tersebut meliputi pengurus Majelis Kesejahteraan Sosial (MKS) Aisyiyah, pekerja sosial profesional (Peksos), hakim pengadilan agama, orang tua kandung/angkat, dan Ketua RT 16 Rawa Makmur, Kota Bengkulu yang bertindak sebagai saksi sejarah komunitas selama 25 tahun untuk kasus-kasus retrospektif masa lalu. Temuan penelitian mengungkap adanya paradoks yudisial di mana hakim mengabulkan 100% permohonan dispensasi akibat kehamilan darurat dan tekanan kuat orang tua untuk menutupi aib sosial, yang sebaliknya justru memicu tingginya angka putus sekolah dan kerentanan sosio-ekonomi jangka panjang. Sebaliknya, Model Perlindungan Anak Aisyiyah terbukti sangat sukses dalam jangka panjang. Dengan menerapkan syarat ketat untuk keberlanjutan pendidikan mutlak, memanfaatkan pemberdayaan ekonomi keluarga yang terstruktur, dan menggerakkan sistem orang tua asuh berbasis komunitas, model ini berhasil mengamankan dimensi hifz al-nafs (perlindungan jiwa) dan hifz al-nasl (perlindungan keturunan). Bukti longitudinal menunjukkan bahwa dengan menghindari pernikahan paksa, ibu remaja sukses meraih gelar sarjana sementara anak-anak mereka tumbuh dewasa (usia 16-20 tahun) dengan kualitas hidup multidimensi yang stabil (hayat tayyibah).